Comparative Efficiency of Different Glazes for Frozen Prawns of Commerce - Cyriac Mathen; T. S. Gopalakrishna Iyer; D. R. Chaudhuri (Fishery Technology, 1970)
Though water is the most common glaze in the preparation of block frozen prawns in India, some processors USC a salt sugar solution or no glaze at all in frozen packs for export. The volume of glaze varies greatly and the usual practice is to add the glaze before freezing till the prawns are just covered. This note reports the results of studies carried out on the effect of these different glazes on the bio chemical, bacteriological and organoleptic quality of prawns during frozen storage.